1987
DOI: 10.1038/325602a0
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in fog

Abstract: The discovery of the very acidic nature of fog and clouds has created much interest in sampling, analysing, and elucidating the chemistry of fog, principally because an understanding of the chemical transformations leading to acid fog may provide important clues to the origin of acid rain. Recently, the knowledge of the chemistry of fog has expanded to include carbonyl compounds, volatile organic acids, and alkyl sulphonates. We have discovered that a variety of pesticides and their toxic alteration products a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0
9

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(119 citation statements)
references
References 20 publications
9
101
0
9
Order By: Relevance
“…In earlier studies atrazine was found in fog, air, arctic ice and seawater even at great distance from urban or agricultural areas (Glotfelty et al, 1987;Chernyak et al, 1996). The detection of atrazine in rainwater, and subsequent deposition of the herbicide from the atmosphere has been reported consistently from places such as Canada, the US and Europe (Brun et al, 2008;Goolsby et al, 1997;Sanusi et al, 2000;Bossi et al, 2002).…”
Section: Elementary Analysis Of Solid Samples Prior To and After As-ementioning
confidence: 90%
“…In earlier studies atrazine was found in fog, air, arctic ice and seawater even at great distance from urban or agricultural areas (Glotfelty et al, 1987;Chernyak et al, 1996). The detection of atrazine in rainwater, and subsequent deposition of the herbicide from the atmosphere has been reported consistently from places such as Canada, the US and Europe (Brun et al, 2008;Goolsby et al, 1997;Sanusi et al, 2000;Bossi et al, 2002).…”
Section: Elementary Analysis Of Solid Samples Prior To and After As-ementioning
confidence: 90%
“…wt. 333 Da), which is regularly found as the transformation product of chlorpyrifos in the atmosphere (Glotfelty et al, 1987;Aston and Seiber, 1997;LeNoir et al, 1999). The mass peak at m/z 335 is contributed from chlorpyrifos oxon with one isotope 37 Cl atom.…”
Section: Resultsmentioning
confidence: 99%
“…4B and 4C arise after the ozone injection. Referring to the previous studies by Racke (1993), Glotfelty et al (1987), Liu et al (2001), Duirk et al (2008) and Bellet and Casida (1974), the mass peak at m/z 333 is assigned to chlorpyrifos oxon (C 9 H 11 Cl 3 NO 4 P, mol. wt.…”
Section: Resultsmentioning
confidence: 99%
“…PCB and organochlorine (ng/g wet mass) and metal (pg/g wet mass) concentrations and % lipid (wet mass) in green frog initial clutches and in tadpoles exposed to water and sediments in field enclosures from 11 June - 26 (Rachel Carson, 1962, Silent Spring) Amphibians first appeared on earth approximately 350 million years ago and have presumably been subjected to naturally-occurring environmental toxicants, such as volcanic gases, which caused massive dieoffs of aquatic animals, or to toxicants in their predators or prey (Duellman andTrueb 1986, Zug 1993 (Glotfelty et al 1987, Kurtz 1990 Although habitat loss is the most frequently cited cause of amphibian declines (Cooke 1972, Bury et a/. 1980, Corn 1994, amphibian declines are also occurring in seemingly pristine, protected areas (Blaustein and Wake 1990) for which habitat loss cannot sE!rve as an explanation.…”
Section: Xx%i%mentioning
confidence: 99%